The development of English company law before 1900 - John D. Turner (Queen's University Centre for Economic History (QUCEH), 2017)
This article outlines the development of English company law in the four centuries before 1900. The main focus is on the evolution of the corporate form and the five key legal characteristics of the corporation - separate legal personality, limited liability, transferable joint stock, delegated management, and investor ownership. The article outlines how these features developed in guilds, regulated companies, and the great mercantilist and moneyed companies. I then move on to examine the State's control of incorporation and the attempts by the founders and lawyers of unincorporated business enterprises to craft the legal characteristics of the corporation. Finally, the article analyses the forces behind the liberalisation of incorporation law in the middle of the nineteenth century.
Keywords: G10; G18; G30; K10; K20; N23; 330; Bubble Act; Company; Corporate Law; Legal Personality; Limited Liability; Transferable Shares; Unincorporated Company